Nesting habits of social wasps (Hymenoptera: Vespidae: Polistinae) in an urban area in the Colombian Caribbean - LÓPEZ-G., YEISON; CANCHILA, SILFREDO; DURÁN, ADRIAN; ÁLVAREZ-G., DEIVYS (Revista Colombiana de Entomología, 2012)
Nesting preferences of social wasps in an urban area of the Colombian Caribbean were studied. The study was carried out in the “campus” of the university of sucre, in sincelejo, Colombia, from March to June of 2011. Nests of social wasps were actively searched for in buildings and surrounding vegetation. for each nest, the species, type of substrate used for nesting, height of the colony in relation to the ground level and developmental state, were recorded.122 nests were found belonging to four genera and eight species, of these Polybia occidentalis venezuelana (27.86%; n = 34), Mischocyttarus sp.1 (25.40%; n = 31), Parachartergus colobopterus (22.95%; n = 28) and Polybia emaciata (16.39%, n = 20) were the most frequent. Polybia occidentalis venezuelana (70.59%; n = 24) and Polybia emaciata (100%; n = 20) preferred to found their nests in the vegetation, while Parachartegus colobopterus (100%; n = 28) and Mischocyttarus sp.1 (96.77%; n = 30) used human constructions as nesting substratum (χ2 = 79.51; P < 0.0001). Most of the swarm-founding wasp colonies were above two meters in height and the most independent-founding colonies were below two meters (χ2 = 61.22; P < 0.0001). The results suggest that the colony phenological pattern of these species is asynchronous.